Assessing earthquake effects on archaeological sites using photogrammetry and 3D model analysis. (June 2018) - Forlin, Paolo; Valente, Riccardo; Kázmér, Miklós
Abstract: This paper evaluates the application of photogrammetric recording to seismically-affected archaeological sites from the moment of on-site data acquisition through to the analysis of the resulting 3D model. This methodology facilitates (i) rapid but accurate recording of seismically-damaged archaeological contexts, (ii) three-dimensional reconstructions, (iii) the documentation of archeological features (e.g. plans, sections, elevations), and (iv) the extraction of additional information and data for archaeoseismological analysis (DEMs, for instance). Not only is greater detail observed using these methods but it can also be quantified at a distance from the target site, thereby extending the researcher's time in the field. 3D photogrammetry and modelling also reduce the risk that small but significant features such as seismic fractures and deformations are overlooked. This paper draws on evidence from two case studies of the EU-funded ArMedEa project (Archaeology of Medieval Earthquakes in Europe, 1000-1550 AD), namely the Islamic fortified village of El Castillejo (Guajar Faragüit, Granada, Spain) and the crusader castle of Saranda Kolones (Paphos, Cyprus).